Study of accumulation of gases in vacuum systems: Measurement of gas transport properties of polymeric films - Chapanian, Rafi (University of Ottawa (Canada), 2004)
In this thesis we have proven that the resistance to accumulation of gases in vacuum tubes is not always negligible. The process of accumulation was described using the Fick's second law of diffusion. The diffusion coefficient was assumed constant and evaluated, depending on pressure, considering Knudsen diffusion, molecular diffusion, or a combination of them. Experimental system with tubes of different lengths and diameters was built and equipped with two high sensitivity pressure transducers to measure the dynamic pressure difference along the system during gas flow experiments. Two cases were considered. First, the governing partial differential equation was solved analytically assuming a constant flow of gas into the system. Experimentally, a low-flow mass flow controller provided the constant flow of gas into the system. In the second case, the governing partial differential equation was solved numerically assuming a time-dependent flow of gas given by the Barrer equation. (Abstract shortened by UMI.)
Keywords: Engineering, Chemical.